Finding shelter : portraits of love, healing, and survival / Jesse Freidin - Freidin, Jesse1981-
In this book, "photographer Jesse Freidin shows the softer side of [the shelter animal] story. He witnessed firsthand how many of the [shelter] volunteers were able to mend their own emotional hurts with the love the shelter animals gave back to them, and how the power of these relationships transforms shelters into places where humans and animals can heal together. This realization propelled him to take a two-year journey across the country to document the tenderness and healing, beauty and joy he encountered within the shelter system"